The validity of coping skills learning media to manage negative emotions for children - Muthmainah, Muthmainah; Purwanta, Edi; Suwarjo, Suwarjo (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2022)
Coping or problem-solving skills need to be trained from an early age. If the child does not have positive coping skills, it is feared that it can cause the child to become maladaptive and stressed. This research aims to test the validity of the learning media for coping skills to manage negative emotions for children aged 4-6. The learning media guidebooks and supporting products, such as posters, emoticon pictures for jumping activities, pictures of emotional expressions, story books, cartoon films, and children's activity sheets. This learning media has a novelty because it focuses on developing media based on children's coping skills that did not exist before. This research is quantitative. This research conducted expert validation to obtain validation and then analyzed quantitatively descriptively. The researcher calculated the validation results with Aiken's V formula. Based on the assessment results from experts, it can be concluded that the learning media for coping skills to manage negative emotions for children aged 4-6 years is declared valid. All items are considered valid because Vtable is 5% greater than Vcount. Guidebooks and supporting products for coping skills to manage children's negative emotions were declared valid and worthy of use for field trials